Impact of chromium histidinate on high fat diet induced obesity in rats - Tuzcu, Mehmet; Şahin, Nurhan; Orhan, Cemal; Agca, Can Ali; Akdemir, Fatih; Tuzcu, Zeynep; Şahin, Kazım (Bmc, 2011)
Background: Chromium (Cr) is an essential trace element that has garnered interest for use as a weight loss aid, but its molecular mechanism in obesity is not clear. In this study, an attempt has been made to investigate the effects of chromium histidinate (CrHis) on glucose transporter-2 (GLUT-2), nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), nuclear factor-kappa B (NF-kappa B p65) and the oxidative stress marker 4-hydroxynonenal adducts (HNE) expressions in liver of rats fed high fat diet (HFD). Methods: Male Wistar rats (n = 40, 8 wk-old) were divided into four groups. Group I was fed a standard diet (12% of calories as fat); Group II was fed a standard diet and supplemented with 110 mu g CrHis/kg BW/d; Group III was fed a HFD (40% of calories as fat); Group IV was fed HFD and supplemented with 110 mu g CrHis/kg BW/d. Results: Rats fed HFD possessed greater serum insulin (40 vs. 33 pmol/L) and glucose (158 vs. 143 mg/dL) concentration and less liver Cr (44 vs. 82 mu g/g) concentration than rats fed the control diet. However, rats supplemented with CrHis had greater liver Cr and serum insulin and lower glucose concentration in rats fed HFD (P < 0.05). The hepatic nuclear factor-kappa B (NF-kappa B p65) and HNE were increased in high fat group compared to control group, but reduced by the CrHis administration (P < 0.05). The levels of hepatic Nrf2 and HO-1 were increased by supplementation of CrHis (P < 0.05). Conclusion: These findings demonstrate that supplementation of CrHis is protective against obesity, at least in part, through Nrf2-mediated induction of HO-1 in rats fed high fat diet.
Keywords: Nf-Kappa-B; Oxidative Stress; Lipid-Peroxidation; Skeletal-Muscle; Body-Weight; Tnf-Alpha; Supplementation; Picolinate; Glucose; Blood